2008
DOI: 10.1038/sj.onc.1211024
|View full text |Cite
|
Sign up to set email alerts
|

The antidiabetic drug metformin exerts an antitumoral effect in vitro and in vivo through a decrease of cyclin D1 level

Abstract: Metformin is a widely used antidiabetic agent, which regulates glucose homeostasis through inhibition of liver glucose production and an increase in muscle glucose uptake. Recent studies suggest that metformin may reduce the risk of cancer, but its mode of action in cancer remains not elucidated. We investigated the effect of metformin on human prostate cancer cell proliferation in vitro and in vivo. Metformin inhibited the proliferation of DU145, PC-3 and LNCaP cancer cells with a 50% decrease of cell viabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
707
5
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(775 citation statements)
references
References 41 publications
49
707
5
14
Order By: Relevance
“…Rapamycin, the inhibitor of mTOR, and its derivatives have been tested in several cancer trials with some success. A study of human prostate cancer cells demonstrated a strong anti-proliferative effect of metformin [13]. This effect was unaffected by inhibition of the AMPK pathway, but was associated with cell cycle arrest in G 0 /G 1 phase, together with a major reduction in cyclin D1 levels.…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin, the inhibitor of mTOR, and its derivatives have been tested in several cancer trials with some success. A study of human prostate cancer cells demonstrated a strong anti-proliferative effect of metformin [13]. This effect was unaffected by inhibition of the AMPK pathway, but was associated with cell cycle arrest in G 0 /G 1 phase, together with a major reduction in cyclin D1 levels.…”
Section: Introductionmentioning
confidence: 99%
“…Mazzone et al reported that diabetes patients with lung cancer who were previously treated with metformin or thiazolidinediones had a lower incidence of metastatic disease at the time of diagnosis and a reduced risk of death compared to those who did not receive the same treatment (4). Thereafter, the antiproliferative action of metformin was confirmed via in vivo and in vitro experiments in various cancer cell lines including breast (5)(6)(7)(8), prostate (9), pancreas (10), and ovarian cancer (11)(12)(13) as well as lung adenocarcinoma (8).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, the precise mechanisms of the metformin-induced effects are not fully understood. In particular, controversy remains about whether metformin is apoptotic (6,10) or just cytostatic (5,9) and whether it kills cancer cells synergistically with cytotoxic agents including cisplatin (11,13), paclitaxel (8), and doxorubicin (17), or if it is antagonistic to cisplatin (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…En accord avec ces résultats, le traitement de cellules cancéreuses du poumon et du sein par la metformine provoque un blocage du cycle cellulaire en phase G2/M et une augmentation de l'apoptose. Dans les lignées cellulaires de cancer de la prostate, la metformine induit un arrêt du cycle cellulaire en phase G0/G1 par l'intermédiaire d'une diminution de l'expression de la cycline D1 [33] (Figure 3). …”
Section: Régulation Du Cycle Cellulaireunclassified
“…Ce résultat a été conforté par de nombreuses évidences obtenues in vitro montrant que la metformine inhibe directement la prolifération des cellules cancéreuses [32,33]. Il est important de noter que la sensibilité des cellules tumorales à la metformine est variable, et l'effet antiprolifératif n'est observé que pour de fortes concentrations de metformine (5-50 mM), bien supérieures à celles obtenues pour un usage thérapeutique chez le diabétique (concentrations plasmatiques de l'ordre de 10 à 40 μM).…”
Section: Effet Antiprolifératif De La Metformineunclassified